2018
DOI: 10.1101/298927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple brain networks mediating stimulus-pain relationships in humans

Abstract: 1The brain transforms nociceptive input into a complex pain experience comprised of 2 sensory, affective, motivational, and cognitive components. However, it is still unclear how pain 3 arises from nociceptive input, and which brain networks coordinate to generate pain 4 experiences. We introduce a new high-dimensional mediation analysis technique to estimate 5 distributed, network-level patterns mediating the relationship between stimulus intensity and 6 pain. In a large-scale analysis of functional magnetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…During chronic pain, the decreased activation incidence of thalamus, S1, S2, IC and ACC is contrasted by increased activation incidence of the pre-frontal cortex (PFC) compared with pain processing in healthy, pain-free individuals (90-92). It is widely agreed that chronic pain states have stronger affective, motivational, and cognitive components and this underpins the preferential activation of the PFC (90, 93). Whilst activity within the PFC was not directly measured in our study, psychological functions associated with these regions were.…”
Section: Discussionmentioning
confidence: 99%
“…During chronic pain, the decreased activation incidence of thalamus, S1, S2, IC and ACC is contrasted by increased activation incidence of the pre-frontal cortex (PFC) compared with pain processing in healthy, pain-free individuals (90-92). It is widely agreed that chronic pain states have stronger affective, motivational, and cognitive components and this underpins the preferential activation of the PFC (90, 93). Whilst activity within the PFC was not directly measured in our study, psychological functions associated with these regions were.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, test-retest reliabilities of individual regions (e.g., amygdala) were much lower ( r s = .11–.27). In a second example, we assessed the same-day test-retest reliability of the neurologic pain signature—a neuromarker for evoked pain—in eight fMRI studies ( N = 228; data from Geuter et al, 2020; Jepma et al, 2018). Reliability was good to excellent in all studies (Fig.…”
mentioning
confidence: 99%
“…Genital arousal levels could in addition be assessed during the fMRI scan (Arnow et al, 2009) and brain response patterns predicting genital arousal levels and self-reported sexual arousal could be compared. This type of study design would allow for a mediation analysis, which could give more insight in the brain organization by examining the distributed, network-level patterns that mediate the stimulus intensity effects on sexual arousal (Geuter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%